2022
DOI: 10.1155/2022/1548390
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Complementary Feeding Practice and Its Associated Factors among Mothers Who Have Children Aged between 6 and 24 Months in Ethiopia: Systematic Review and Meta-Analysis

Abstract: Background. Appropriate complementary feeding practices prevent malnutrition among children. The proportion and determinant factors of appropriate complementary feeding practices identified by different studies were inconsistent in Ethiopia. Therefore, this systematic review and meta-analysis aimed to assess the pooled proportion and determinants of appropriate complementary feeding practices among mothers. Methods. Databases (PubMed, HINARI, Google Scholar, Cochrane Library, and Web of Science) and university… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
1
0
0
Order By: Relevance
“…This study identified that the mothers who received counseling on IYCF had higher odds of practicing appropriate complementary feeding (AOR: 4.2, CI: 1.5–12.3) in compression to those who did not receive any counseling. This finding is supported by studies done in Ethiopia [ 14 , 15 , 29 ], Nepal [ 9 ], and Nigeria [ 30 ].…”
Section: Discussionsupporting
confidence: 78%
“…This study identified that the mothers who received counseling on IYCF had higher odds of practicing appropriate complementary feeding (AOR: 4.2, CI: 1.5–12.3) in compression to those who did not receive any counseling. This finding is supported by studies done in Ethiopia [ 14 , 15 , 29 ], Nepal [ 9 ], and Nigeria [ 30 ].…”
Section: Discussionsupporting
confidence: 78%